Embedding Halal Values in Organizational Culture: Implications for Service Quality and Customer Satisfaction - Hadi, Hafid Kholidi; Zhulqurnain, Mohamad Rijal Iskandar (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
The rapid growth of the global halal industry has increased the need for organizations to move beyond symbolic halal compliance and integrate Islamic values into their internal management practices. This study aims to examine the role of halal organizational culture as a driver of service quality and customer satisfaction in halal-oriented service organizations. Using a quantitative research design, data were collected from 170 customers who had experienced services provided by halal-based organizations. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that halal organizational culture has a positive and significant effect on service quality and customer satisfaction. Service quality is also found to significantly influence customer satisfaction and plays a mediating role in the relationship between halal organizational culture and customer satisfaction. These results indicate that halal values embedded in organizational culture enhance customer satisfaction primarily through improvements in service quality. This study contributes to the halal and service management literature by highlighting the importance of internal organizational culture in shaping service outcomes and customer perceptions. Practically, the findings suggest that managers of halal-oriented organizations should focus on cultivating a strong halal organizational culture and translating Islamic values into concrete service practices to achieve service excellence and sustainable competitive advantage.